2015
DOI: 10.1111/jth.12956
|View full text |Cite
|
Sign up to set email alerts
|

Carboxypeptidase B2 deficiency reveals opposite effects of complement C3a and C5a in a murine polymicrobial sepsis model

Abstract: Summary Background and Objectives Carboxypeptidase B2 (CPB2) is a basic carboxypeptidase with fibrin and complement C3a and C5a as physiological substrates. We hypothesized that in polymicrobial sepsis, CPB2-deficient mice would have sustained C5a activity, leading to disease exacerbation. Methods Polymicrobial sepsis was induced by cecal ligation and puncture (CLP). Results Contrary to our hypothesis, Cpb2−/− mice had significantly improved survival, with reduced lung edema, less liver and kidney damage,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
30
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 50 publications
(63 reference statements)
7
30
0
1
Order By: Relevance
“…A role for CPB2 in protection against sepsis is consistent with data showing that CPB2 levels in the cerebrospinal fluid correlate with the severity of disease and the levels of complement activators such as C3a, iC3b, and C5b‐9 . In a polymicrobial sepsis model, Cpb2 − / − mice were protected and the relevant physiological substrate causing the phenotype was shown to be C3a, although both C5a and fibrin also played a role in the disease . This is consistent with the hypothesis that C3a plays an essential role in stimulating peritoneal macrophages to combat the infection, whereas C5a and fibrin exacerbate the outcome.…”
Section: Roles For Cpb2 Explored In Cpb2−/− Micesupporting
confidence: 86%
“…A role for CPB2 in protection against sepsis is consistent with data showing that CPB2 levels in the cerebrospinal fluid correlate with the severity of disease and the levels of complement activators such as C3a, iC3b, and C5b‐9 . In a polymicrobial sepsis model, Cpb2 − / − mice were protected and the relevant physiological substrate causing the phenotype was shown to be C3a, although both C5a and fibrin also played a role in the disease . This is consistent with the hypothesis that C3a plays an essential role in stimulating peritoneal macrophages to combat the infection, whereas C5a and fibrin exacerbate the outcome.…”
Section: Roles For Cpb2 Explored In Cpb2−/− Micesupporting
confidence: 86%
“…Compstatin, a synthetic C3 convertase inhibitor, not only inhibited complement activation during E. coli sepsis in baboons, but also attenuated other inflammatory responses, coagu lation activation and multiple organ failure 13 . The receptors for C3a and C5a may have differential roles in sepsis, as indicated by a recent study in which treatment with a C5a receptor antagonist improved survival during polymicrobial sepsis, whereas the administration of a C3a receptor antagonist reduced survival 14 .…”
Section: Complement Activation Complement Activation Resultsmentioning
confidence: 95%
“…Studies using the Cpb2 ‐deficient ( Cpb2 −/− ) mouse confirm that the observed in vitro inactivation of complement C3a and C5a by CPB2 also occurs in vivo . Cpb2 −/− mice developed more severe alveolitis than WT mice upon tracheal instillation of C5a .…”
Section: Introductionmentioning
confidence: 78%